Keamanan Investasi Online: Evaluasi Regulasi Perlindungan Investor dalam Konteks Robot Trading di Indonesia - Rizzal, Muhammad Saeful; Rustan, Ahmad; Ichlas, Rudy Iskandar (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2024)
Investment has become a new lifestyle for some people, as investment promotions typically entice potential investors with promising returns. In Indonesia, investments are broadly categorized into tangible and financial investments. This study aims to review the licensing system and protection for victims of online robot trading investments in Indonesia, focusing on safeguarding the public as investors. This research aims to provide knowledge so that the public can differentiate between legal and illegal investments, thus encouraging more cautious investment decisions. The method employed in this study is a normative juridical approach involving an analysis of existing laws and regulations, including the Consumer Protection Law, Capital Market Law, and regulations issued by the Financial Services Authority (OJK). A qualitative analysis of the collected data was conducted to assess the extent to which current regulations can protect the public from potential losses arising from investments in robot trading. The research findings indicate that the protection of victims in online robot trading investments in Indonesia needs to be strengthened and adapted to technological and market developments. Stricter and more specific regulations governing the operations of robot trading platforms are necessary. It is advisable for the public to exercise caution when engaging in online investments to avoid becoming victims.